Mediación didáctica de actividades musicales para la convivencia escolar en 5° de primaria (2022)
Technological advances in neuroimaging techniques have made it possible to verify, with greater certainty, what happens in the brain when it is exposed to a flow of stimuli of various kinds. In fact, many studies have demonstrated the effect of movement, singing and music on the physical, psychological and social levels, which allows us to infer that musical activities can be an effective tool for their application in students with academic and social difficulties. We consulted research that demonstrates the great influence of music at the cerebral level, as well as in human learning and in society, and took as theoretical bases Empiricism, Associationism, Behaviorism, Vygotski's theory, Piagetian theory, the theory of Multiple Intelligences, the VAK learning model, the BAPNE method, and methods for the teaching and learning of music such as Dalcroze, Kodály, Willems and Orff. The research was developed under the introspective-experiential approach from the perspective of the qualitative paradigm and, taking into account the analysis and scope of the work, with a descriptive-propositive type of research, which allowed us to provide a possible alternative solution for the transformation of the reality of the actors. Despite the significant differences between the two institutions with respect to educational context, socioeconomic status, academic level, curriculum, pedagogical model, population, among others, important points in common could be observed, which allowed establishing, by way of conclusion, similarities in terms of physical condition, cognitive development and psychosocial characteristics